Dialectical Thinking and the Spirit of Transformation: The Enduring Value of Laozi’s Philosophy in a Fractured Age - Hanh, Luyen Thi Hong; Tam, Le Thi; Len, Nguyen Thi (Journal of Posthumanism, 2025)
Amidst the uncertain turns of this era, where once self-evident values are fracturing, and humanity is constantly swept into irreconcilable conflicts with no way out-the thought of Laozi, crystallized over two thousand years ago in the Tao Te Ching, emerges as a unique philosophical anchor rich in healing potential. Not bearing the markings of a rigid dogmatic system or inflexible doctrine, Laozi’s philosophy is like a gentle mist, penetrating the darkest corners of modern life, where reason appears to have reached the very limits of its capacity. This article begins from a premise: that philosophy is not only contemplation but also a way of life—a “spiritual practice.” From that foundation, the author approaches Laozi’s thought as a dynamic philosophical system—where being is not confined to fixed concepts but always moves and transforms in rhythm with the Tao. The dialectical thinking in Laoist philosophy, therefore, is not a model of antithesis-synthesis as in Hegel, but a form of “soft dialectics”: it neither negates nor imposes but transforms, complements, and circulates in harmonious relation. With that approach, the article focuses on analyzing two primary dimensions in Laozi’s dialectical thought: (1) the principle of opposition and unity between paired categories such as Being – Non-being, Hard – Soft, High – Low... and (2) the understanding of cyclical movement in nature and society. Passages from the Tao Te Ching are used as vivid evidence of Laozi’s prophetic capacity and philosophical depth. Sayings such as “Being arises from Non-being” (Ch. 40), “The soft overcomes the hard” (Ch. 78), or “Blessing and calamity lean on each other” (Ch. 58) are not merely concise depictions of natural laws but also actionable guidance for all humanity in an age of upheaval. The article’s emphasis lies in the connection between Laoist dialectics and modern issues—from ecology, politics to social governance. In a context where the world is facing global crises—climate change, power conflicts, moral decline—Western philosophy, with its tendencies toward dualism, absolutism, and forceful intervention into nature, is revealing certain limitations. In contrast, Laozi’s philosophy—with its foundations in “non-action” (wu wei), “knowing sufficiency” (zhi zu), and “holding to the center” (shou zhong)—offers a countercurrent approach: acting by not acting, possessing by not striving, achieving effectiveness by letting go of coercive desire. From a methodological perspective, the article employs a hermeneutic-philosophical approach combined with comparative analysis, placing passages from the Tao Te Ching alongside dialectical models in Western thought such as Hegel, Heraclitus, Deleuze… to illuminate both the convergence and divergence between the two systems. While Hegel follows a linear trajectory: affirmation – negation – synthesis, Laozi prefers the cycle: emergence – rise – flourish – decline – return. While Deleuze exalts “difference as becoming,” Laozi emphasizes “co-birth in opposition.” This comparison does not aim to force Eastern thought into Western frameworks, but to reveal the resonance among wisdom traditions—where distinct paradigms can illuminate each other. More importantly, the dialectical thought in Laozi’s philosophy does not stop at explaining the world but opens a path toward humane and sustainable action. The idea that “governing a country is like cooking a small fish” (Ch. 60) is a reminder of the limits of coercive power. “Not contending, and none in the world contend with him” is a message to leaders about the power of humility. And “non-action, yet nothing is left undone” is a global principle for social governance, self-management, and peace-building. Throughout the article’s length, one consistent message is clearly conveyed: Laozi’s thought is not an outdated framework, nor is it merely an ornamental piece of Eastern culture. On the contrary, it is a source of spiritual vitality, a soft weapon for a humanity teetering between ambition and limitation, growth and collapse. If Hegel or Marx once believed in an absolute endpoint, Laozi shows that the absolute lies not in the destination but in the process itself, in each step aligned with the Tao. In conclusion, this article affirms that Laozi’s dialectical thought is a philosophy of harmony and transformation—not only holding theoretical value but also opening a way of life, a direction for a world that has lost its bearings. In an era where instrumental reason and radical individualism dominate, Laozi’s philosophy is a quiet yet steadfast reminder: that humanity need not conquer the world, but simply learn to live with it—in alignment with the Tao—like water, like wind, invisible yet infinite.